(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article scientifically analyzes the reforms implemented in the higher education system in the Republic of Uzbekistan in the post-independence period, especially in recent years, their content and results. It covers regulatory and legal documents and practical measures aimed at modernizing higher education, improving the quality of education, adapting it to international standards, and training competitive personnel. It also substantiates the prospects for the development of the higher education system, existing problems and ways to overcome them.